2021
DOI: 10.2991/absr.k.210621.029
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Aspects of Mentawai Traditional Agricultural System (Pumonean) and Its Implications for the Conservation of Local Germplasm in Siberut, Mentawai, Indonesia

Abstract: Mentawai people have a unique agricultural tradition. The traditional agricultural system (mone) is adaptive, using the plants that are suitable for the landscape. Land clearing is carefully done without destroying the entire forest. We conducted ethnobotany studies to explore the composition and the structure of the plants used in the traditional plantation (Pumonean) as well as their values for the Mentawai people in the Siberut island. We surveyed the agricultural system employed by Mentawai people and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It was found that the Mone land had a wide tree canopy and functioned more as a conservation area, whereas the Tinugglu land was used for short-lived agriculture. Research by Nurainas et al (2020) in several Siberut forest locations also showed that the highest LUVI was also found in the Metroxylon sago, Durio zibethinus and Arthocarpus integer types. Furthermore, Nopiansyah et al (2016), findings indicate that the traditional communities on Siberut Island continue to rely on forest resources, even though their utilization practices have evolved in recent times, incorporating new technologies.…”
Section: Discussionmentioning
confidence: 90%
“…It was found that the Mone land had a wide tree canopy and functioned more as a conservation area, whereas the Tinugglu land was used for short-lived agriculture. Research by Nurainas et al (2020) in several Siberut forest locations also showed that the highest LUVI was also found in the Metroxylon sago, Durio zibethinus and Arthocarpus integer types. Furthermore, Nopiansyah et al (2016), findings indicate that the traditional communities on Siberut Island continue to rely on forest resources, even though their utilization practices have evolved in recent times, incorporating new technologies.…”
Section: Discussionmentioning
confidence: 90%
“…We found 51 species from 14 genera in the Zingiberaceaae family have been utilized by the people in West Sumatra in six categories of utilization [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The flow chart shows that the most common utilization of Zingiberaceae in West Sumatra is as a medicine, followed by utilization as a spice, culture, fruit, vegetable, and natural dye (Fig.…”
Section: Traditional Uses Of Zingiberaceaementioning
confidence: 99%
“…We found that the people who live in West Sumatra make use of 51 different species from 14 different genera that are a part of the Zingiberaceae family [23,[26][27][28][32][33][34][35][36][37][38][39][40][41][42]. These uses fall into six different categories.…”
Section: Potential Uses Of Zingiber Album Among Other Of Zingiberacea...mentioning
confidence: 99%